A Product on Double Cosets of B∞ - Gonzalez Pagotto, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
For some infinite-dimensional groups G and suitable subgroups K, there exists a monoid structure on the set K∖G/K of double cosets of G with respect to K. In this paper, we show that group B∞, of the braids with finitely many crossings on infinitely many strands, admits such a structure.